Grain refinement of 2Mn-0.1C steel by repetitive heat treatment and recrystallization. Issue 1 (July 2015) - Park, M H; Shibata, A; Tsuji, N
Abstract: Grain refinement in metals is well-known as one of the most effective methods to enhance their strength without addition of other elements. In this study, repetitive heat treatment combined with subsequent cold-rolling and recrystallization were investigated to obtain ultrafine-grained ferrite. Ultrafine-grained (UFG) ferritic structure having a mean grain size smaller than 1 μm was fabricated by repetitive heat treatment at 810 °C for 180 s and cold rolling by 90% plus a recrystallization heat treatment at 600 °C. Starting from this UFG ferrite, finegrained dual phase (DP) steel composed of ferrite and martensite phases with grain sizes smaller than 3 pm could be also obtained by intercritical heat treatment at 740 °C for 30 minutes followed by water-quenching. The mechanical properties of the ultrafine-grained ferritic and DP structured specimens were evaluated by tensile test. Results of the tensile test showed that finegrained ferritic and DP structures had higher yield and tensile strength than the coarse-grained ferritic and DP structures of the same steel.